THE CHALLENGE OF APPLYING COMPETENCY-BASED TEACHING AND STUDENT-CENTERED INSTRUCTIONS IN A HIGHER EDUCATION LEVEL - Lilies Setiasih (Universitas Islam Bandung, 2014)
An organizational environment has undergone dramatic change lately. A company, in order to win the competition in the long run, should have the right strategy. One of the main tasks of a leader associated with the management of human capital is how to encourage optimal performance of the organization human resources in order to achieve predetermined goals. One approach in the management of human resources is a competencybased human resource management (CBHRM). By this system, it is expected that leaders are able to see a match employees with the rank to which it aspires. Therefore, an integrated system that requires competencies possessed human capital can be aligned with corporate goals. The successful implementation of CBHRM in this study could be measured by using 5 (five) dimensions, i.e., alignment, integration, distribution, self-directed application, and acculturation. The unit of analysis in this study were the energy sector state-owned companies in Indonesia, because these companies have a strategic role in the economy in Indonesian, especially to ensure the source availability of energy supply to drive industries in The process of production, consumption , as well as a source of foreign exchange earnings . The population of this study were 5 (five) energy sector companies in Indonesia. The unit of observation in this study was represented by the 38 Secondary Managers, 67 Line Managers and 140 employees of state-owned energy sector companies in Indonesia, where the 245 respondents spread over 25 (twenty five) regions in Indonesia. The results showed that the implementation of CBHRM in the state-owned energy sector companies in Indonesia have been achieved well, after the significance testing, the null hypothesis was rejected and the alternative hypothesis was accepted. It means that the implementation of research variable achieved well.